Implementation of Supervision by the Secretary in Efforts to Achieve Effectiveness of Archives Management at the Secretariat of the Cooperatives and SMEs Office of North Sumatra Province - Chairani, Zizah; Arif , Muhammad (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
In connection with the preparation of the research entitled "Implementation of Supervision by the Secretary in Efforts to Achieving Effectiveness of Archives Management at the Secretariat of the Cooperatives and SMEs Office of North Sumatra Province" the author conducted a study to find out how far the relationship between supervision and archive management is at the Secretariat of the Cooperatives and SMEs Office of North Sumatra Province which is a one of the indicators that can be used as a benchmark for the success of the implementation of tasks and functions at the Service. The research method used is descriptive analysis method, which is a research method that systematically describes the implementation of supervision by the secretary in an effort to achieve the effectiveness of archive management at the Secretariat of the Office of Cooperatives and SMEs of North Sumatra Province. The implementation phase of the research was carried out by means of observation and interviews. Based on the author’s observations during the research at the Department of Cooperatives and SMEs of North Sumatra Province, it turns out that there are still some indications of problems that indicate that the effectiveness of archive management at the agency has not been maximized. The problem is suspected because the Secretary of the North Sumatra Province Cooperatives and SMEs Office in the implementation of supervision has not been optimal.